Suptulung as indigenous knowledge of Kirat Rai people - Rai, Shanti Devi (Siddhajyoti Interdisciplinary Journal, 2020)
Among the indigenous peoples around the world, Rai people belong to the Kirat community. Mundhum is their religio-cultural philosophy, which is practiced orally in their everyday lifestyle with full of ritual activities. Suptulung composed by three stones that hold spiritual and cultural meanings to the community. According to their belief, the Suptulung as one of the main shrines of the household is the sacred place, from where the development and enhancement of knowledge emanates. All rituals and rites from birth to death conducted herein oral form. Suptulung is their main identity and holds cultural importance too. Their spirituality or supernaturalism is connected to nature, as they are nature-worshippers and nature- protectors. As an indigenous belief system and marginalized cultural practice, Suptulung is on the verge of extinction due to the mainstream socio-cultural pressures as well as marginality. Although this oral tradition performance at Suptulung has been continuing generation to generation yet, is facing serious hard times. It is so because its educational value as a form of indigenous knowledge system has not been realized in federal, provincial and local level curriculum. In this article, I have used primary data and discussed the knowledge of Suptulung and Mundum, which support to understand Mundumic education.